2021
DOI: 10.1080/14680629.2021.1906305
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of warm mix asphalt incorporating steel slag and high reclaimed asphalt for wearing courses: a case study

Abstract: This study quantifies the potential environmental benefits associated with the incorporation of industrial by-products and recycled materials combined with warm mix asphalt (WMA) additives in wearing course mixtures for asphalt pavement construction. An electric arc furnace (EAF) steel slagbased mix and three recycled mixtures incorporating steel slag and fractionated reclaimed asphalt (RA) of varying contents (i.e. 25, 40, and 50%) were analyzed comparatively to reference hot mix asphalt (HMA) using the 'crad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Nevertheless, the results of this study generally indicate that high reclaimed asphalt content (up to 50%) and steel slag can be valorized towards developing circular, resource-efficient, and durable anti-skid wearing course mixtures. It was also demonstrated that these mixtures offer significant environmental benefits [ 38 ], and therefore can be considered to be a promising sustainable solution for full-scale implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results of this study generally indicate that high reclaimed asphalt content (up to 50%) and steel slag can be valorized towards developing circular, resource-efficient, and durable anti-skid wearing course mixtures. It was also demonstrated that these mixtures offer significant environmental benefits [ 38 ], and therefore can be considered to be a promising sustainable solution for full-scale implementation.…”
Section: Discussionmentioning
confidence: 99%
“…8 To evaluate the environmental feasibility of asphalt pavement modified by waste plastics and EAFSS, several recent LCA studies were considered. [12][13][14][15][16][17] Table 1 presents a summary of these research in terms of pavement layers, type of mixtures, waste materials, system boundary, and avoided impacts. It should be noted that "system boundary" refers to the processes investigated by the LCA, "avoided impacts" indicates the impacts of the processes that are avoided by using waste PE and EAFSS in pavements.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that "system boundary" refers to the processes investigated by the LCA, "avoided impacts" indicates the impacts of the processes that are avoided by using waste PE and EAFSS in pavements. It can be seen that most studies focus on the surface course of pavements using HMA, while Ferreira et al (2016) 12 also includes the base course and Georgiou and Loizos (2021) 14 considers warm mix asphalt (WMA). Moreover, the research in Table 1 mainly investigates waste plastics or EAFSS individually, except Georgiou and Loizos (2021) 14 and Yao et al (2022) 16 , which also incorporate reclaimed asphalt pavement (RAP) into asphalt mixtures with waste plastics or EAFSS modifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recycling the old asphalt pavement is a common operation used worldwide for saving natural materials, investment, and energy in highway maintenance projects [1][2][3][4]. In practice, the hot-mix recycled asphalt mixture (RHMA) has similar durability and performance to the conventional dense asphalt mixture if the RAP content is limited at 10-40%, depending on the design of mixture [5][6][7].…”
Section: Introductionmentioning
confidence: 99%